2022
DOI: 10.3389/fpls.2022.922797
|View full text |Cite
|
Sign up to set email alerts
|

Symptom recognition of disease and insect damage based on Mask R-CNN, wavelet transform, and F-RNet

Abstract: Brown blight, target spot, and tea coal diseases are three major leaf diseases of tea plants, and Apolygus lucorum is a major pest in tea plantations. The traditional symptom recognition of tea leaf diseases and insect pests is mainly through manual identification, which has some problems, such as low accuracy, low efficiency, strong subjectivity, and so on. Therefore, it is very necessary to find a method that could effectively identify tea plants diseases and pests. In this study, we proposed a recognition f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…It was consistent with prior research findings. In our team’s study by Li et al [ 29 ], five models, F-RNet, ResNet18, VGG16, AlexNet and SVM, were developed to identify three tea pests and disease symptoms. The results showed that the deep learning models such as ResNet18, VGG16 and AlexNet had 82%, 80% and 73% accuracy, respectively, which were significantly greater than the SVM machine learning model with 65% accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was consistent with prior research findings. In our team’s study by Li et al [ 29 ], five models, F-RNet, ResNet18, VGG16, AlexNet and SVM, were developed to identify three tea pests and disease symptoms. The results showed that the deep learning models such as ResNet18, VGG16 and AlexNet had 82%, 80% and 73% accuracy, respectively, which were significantly greater than the SVM machine learning model with 65% accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…To better extract the feature information of the leaves of tea coal disease, the images of the diseased leaves were enhanced by wavelet transform. [ 29 ]This is because the wavelet transform enhancement processing applied in previous studies has made good progress in improving model accuracy, and the model has strong generalization ability and is suitable for tea tree disease classification. Wavelet transform can reduce or remove the correlation between different features of the extracted diseased leaf images by selecting appropriate filters.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2 Technique role of tea plant monitoring on leaf-scale [6,11,12] RNet) based on R-CNN and wavelet trans-form on RGB images to identify the diseases and pests of tea leaves. Karmokar et al [14] developed a tea leaf disease identifier that integrates a neural network to recognize diseases by extracting features from tea leaf images.…”
Section: Disease Leaf Segmentationmentioning
confidence: 99%
“…Singh [8] used multilayer convolutional network MCNN to classify mango anthracnose leaf disease with 97.3% accuracy. He [9] proposed a Mask-RCNN based model for detecting leaf diseases of tea tree with F1 scores of 88.3% and 95.3% for tea coal diseases and boll weevil leaf diseases, but the F1 scores was lower in distinguishing between brown leaf disease and target spot disease, with scores of only 61.1% and 66.6%. The analysis showed that the two-stage detection model needs to generate candidate frames before target classification and bounding box regression, which is difficult to apply because of high model complexity, slow speed, and low accuracy, although it can identify crop diseases.…”
Section: Introductionmentioning
confidence: 99%